CT Imaging of Gastrointestinal Stromal Tumour: Case Report and Literature Review - Dineva, Stoyanka; Mlachkova, Dobrina; Todorov, Deyan (International Journal For Research In Health Sciences And Nursing, 2017)
A gastrointestinal stromal tumour (GIST) is a type of soft tissue sarcoma that develops in the digestive tract. Gastrointestinal stromal tumors (GIST) are the most common mesenchymal neoplasms of the gastrointestinal tract with a malignant potential. However, uncommonly they can be associated with synchronous tumors of different histogenesis. Most GISTs begin in the stomach or small bowel, but they can develop anywhere along the digestive tract. About 6 out of 10 (60%) of these tumours start in the stomach. Very rarely, they develop outside the gastrointestinal tract.